Clinical impact of child life intervention combined with comprehensive nutrition intervention on pain management, nutritional status, and treatment compliance in school-age children with limb fractures - Zhang, Qin; Jin, Fangqin; Weng, Jiangping; Pan, Xuting; Dong, Qinyan; Zhao, Yuping; Sheng, Jiaojiao (Frontiers in Medicine, 2025)
BackgroundFractures of the limbs are a common health problem among school-aged children and can cause severe pain as well as emotional issues. Traditional care may not fully meet the comprehensive needs of these children. Therefore, exploring more comprehensive intervention measures is of significant clinical importance.ObjectiveThis research aimed to evaluate the clinical effect of Child Life intervention combined with a comprehensive nutrition intervention on pain management, nutritional status, and treatment compliance of school-age children with limb fractures.MethodsA total of 100 school-age children with limb fractures treated in our hospital from March 2024 to September 2024 were selected and randomly divided into a control group (CG) and an observation group (OG) using the random number table method, with 50 cases in each group. The CG received conventional nursing intervention, while the OG received Child Life intervention and comprehensive nutrition intervention on the basis of the CG. The pain scores, serum cortisol levels, treatment compliance, and nutritional status in both groups before and after surgery were compared.ResultsAt 12 h and 24 h after surgery, the FLACC scores in the OG were lower than those in the CG (p < 0.001, t = 5.042; p < 0.001, t = 4.836). At 12 h and 24 h after surgery, serum cortisol level in the OG exhibited depletion relative to that in the CG (p < 0.001, t = 6.049; p < 0.001, t = 11.662). After intervention, treatment compliance in the OG was higher than that in the CG, indicating statistical significance (p = 0.037, χ2 = 4.332; p = 0.017, χ2 = 5.741; p = 0.025, χ2 = 5.005). At 24 h after surgery, Lc, HGB, PA, and ALB levels in the OG were higher than those in the CG, indicating statistical significance (p < 0.01, t = 2.717; p < 0.001, t = 3.433; p < 0.001, t = 5.023; p < 0.001, t = 4.230).ConclusionA combination of Child Life intervention and comprehensive nutrition intervention can enhance the pain management effect in school-age children with limb fractures, attenuate their pain level, ameliorate their perioperative stress status, and improve their postoperative nutritional status, accelerating their recovery.